A beautiful new species of Hyalonthophagus Palestrini & Giacone, 1988 (Coleoptera: Scarabaeidae: Scarabaeinae), from the Northern Cape Province, South Africa - Deschodt, Christian M.; Davis, Adrian L.v.; Sole, Catherine L. (Zootaxa, 2019)
Hyalonthophagus Palestrini & Giacone, 1988, from Afrotropical savanna, is raised to generic status having been originally described as a subgenus within the genus Onthophagus Latreille, 1802. Hyalonthophagus pulcher Deschodt & Davis, new species is described from the Northern Cape, South Africa. Maps are provided to show (1) the locally-restricted distribution pattern of the new species isolated from adjoining savanna in warm, dry Karoo climate to the south of the Orange River, and, (2) the disjunct distribution pattern in relation to those of three other southern African species centred in savanna to the northeast beyond areas with unsuitable climatic or ecological conditions. An assessment of the conservation status for Hyalonthophagus pulcher Deschodt & Davis, new species is also provided.